An investigation on usability of 3D visualization and simulation programs in leather apparel. Issue 8 (25th July 2022) - Ork Efendioglu, Nilay; Mutlu, Mehmet Mete; Pamuk, Oktay
Abstract: Three-dimensional (3 D) visualization and simulation programs cannot be used in leather apparel companies prevalently due to the lack of leather material information in the databases. In this study, the properties of different types of leather and fabrics are determined with certain standards and alternatively with FAST (Fabric Assurance by Simple Testing) system, interpreted and defined in the database of Vidya 3 D program. The two-dimensional (2 D) garment patterns prepared in the Assyst CAD program were transferred to the 3 D program, and dress simulations were performed on the virtual mannequin by using the newly defined materials. The sewn dresses and simulations were evaluated by a jury considering similarity success. It has been found that Vidya 3 D program can simulate model and material behaviors realistically by using the data obtained from the FAST system, however, it does not demonstrate the drape parameter precisely, and the software should be improved for this direction.